A Stochastic Approach Analysing Enterprises' Investment following Financing Reform in China. (1st August 2022) - Xiao, Shuxing; Li, Guangliang; Zhang, Weikun; Zhou, Mingming; Zheng, Wolin
Abstract : This paper explores the change of enterprises' investment following the financing system reform through the established stochastic investment model. In this constructed model, financing property, market-oriented reform, and government intervention are regarded as a stochastic process. Furthermore, the modern China's economic situation is interpreted to analyze the enterprises' investment by government intervention plan combined with he deduced proposition from the stochastic investment model. The results provide a depth understanding for characteristics of the enterprise in China that the steady capital of state-owned enterprises' investment is higher than that of non-state-owned enterprises without government intervention before completing financing reform. Although government intervention can increase the investment level of state-owned enterprises, doing so increases the turbulence of the market economy. Additionally, the impact of government-led financing reform on enterprises' investment is asymmetrical. Promoting market-oriented, clear-cut financing reform, and reducing government-led investment plans will improve enterprises' investment efficiency and stabilize China's economic development. The present paper provides a specific future orientation of China's financing reform determining the level of enterprises' investment.